PENERAPAN ERGONOMI K3 DALAM PROSES PENGELASAN - Yusmita, Yesi; Hasanah, Hijratul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
The process of electric welding is a welding process using webbed electrodes as an added source of heat from current power. From the ergonomic aspect that needs to be improved is the light intensity and airflow in the workplace. The purpose of this study was to determine the decrease in workload, musculoskeletal complaints and increase work productivity in students. This research was conducted with a total sample of 5 people, the experimental research method used the same subject design (treatment by subjects design). This research activity aims to increase the knowledge and skills of welders in welding activities based on welding safety and health standards (WSH).